2017
DOI: 10.3389/fmars.2017.00370
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Primary Production in the Canary Current Upwelling System—A Regional Perspective Comparing Remote Sensing Models

Abstract: After Bakun (1990) formulated his hypothesis of upwelling intensification caused by increasing global warming, contradictory results have been published on whether primary productivity is increasing or decreasing in Eastern Boundary Upwelling Ecosystems (EBUE). The present work is focused in comparing three net primary production (NPP) models-the VGPM (Vertically Generalized Production Model), the Eppley-VGPM and the CbPM (Carbon-based Production Model)-in the Canary Current (CanC) EBUE during the 1998-2015 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 52 publications
4
48
0
1
Order By: Relevance
“…A progressive warming and decreasing productivity over the last two decades was suggested for the CC‐EBUEs as a whole (Arístegui et al, ), which would better match our flux records from the deep ocean sediment traps than the Bakun et al (, ) scenario of coastal upwelling intensification. Barton et al () and Gómez‐Letona et al () also found no evidence of increasing alongshore winds and productivity in the Canary Current System. However, one should keep in mind that the CC‐EBUEs is characterized by various subsystems which could react differently to global warming (e.g., Arístegui et al, ; Garcìa‐Reyes et al, ; Lathuilière et al, ; Sydeman et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…A progressive warming and decreasing productivity over the last two decades was suggested for the CC‐EBUEs as a whole (Arístegui et al, ), which would better match our flux records from the deep ocean sediment traps than the Bakun et al (, ) scenario of coastal upwelling intensification. Barton et al () and Gómez‐Letona et al () also found no evidence of increasing alongshore winds and productivity in the Canary Current System. However, one should keep in mind that the CC‐EBUEs is characterized by various subsystems which could react differently to global warming (e.g., Arístegui et al, ; Garcìa‐Reyes et al, ; Lathuilière et al, ; Sydeman et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Products that combine SSH and drifter measurements have improved eddy kinetic energy and dynamic topography estimates (Maximenko et al, 2009;Lumpkin and Garzoli, 2011;Rio et al, 2014;Rio and Santoleri, 2018). Estimates of chlorophyll derived from satellite ocean color measurements provide information on biological productivity in boundary current systems worldwide (e.g., Messié and Chavez, 2015;Gómez-Letona et al, 2017). Because ocean color observations have higher resolution (O(1) km) than satellite altimetry measurements, they potentially provide insight into the rich fields of submesoscale instabilities that exist within boundary current systems (Figure 4; Everett et al, 2014;Lee and Kim, 2018).…”
Section: Remote Sensingmentioning
confidence: 99%
“…It has been noted that NPP can be influenced by varying climatic patterns [26], [82], [83] in different geographical areas other than the Red Sea. We analyzed different climate indices for their impact on the NPP products derived from the previously mentioned models.…”
Section: B Comparison With Climate Indicesmentioning
confidence: 99%